Continuous neurally adjusted ventilation: a feasibility study in preterm infants. Issue 6 (8th April 2020) - Rochon, Marie-Eve; Lodygensky, Gregory; Tabone, Laurence; Essouri, Sandrine; Morneau, Sylvain; Sinderby, Christer; Beck, Jennifer; Emeriaud, Guillaume
Abstract : Objectives: To assess the feasibility and tolerance of NeuroPAP, a new non-invasive ventilation mode which continuously adjusts (during both inspiration and expiration) the pressure support proportionally to the diaphragm electrical activity (Edi), in preterm infants and to evaluate the impact on ventilation pressure and Edi. Design: Prospective cross-over single-centre feasibility study. Setting: One level 3 neonatal intensive care unit in Canada. Patients: Stable preterm infants ventilated with non-invasive positive pressure ventilation (NIPPV). Interventions: Subjects were successively ventilated in NIPPV with prestudy settings (30 min), in NeuroPAP with minimal pressure similar to NIPPV PEEP (positive end-expiratory pressure) (60 min), in NeuroPAP with minimal pressure reduced by 2 cmH2 0 (60 min), in continuous positive airway pressure (15 min) and again in NIPPV (30 min). Main outcome measures included tolerance, ventilation pressure, Edi and patient-ventilator synchrony. Results: Twenty infants born at 28.0±1.0 weeks were included. NeuroPAP was well tolerated and could be delivered during 100% of planned period. During NeuroPAP, the PEEP was continuously adjusted proportionally to tonic diaphragm Edi, although the average PEEP value was similar to the set minimal pressure. During NeuroPAP, 83 (78–86)% breaths were well synchronised vs 9 (6–12)% breaths during NIPPV (p<0.001). Conclusions: NeuroPAP is feasible and well tolerated in stable preterm infants, and it allows transient adaptation in PEEP in response to tonic diaphragm electrical activity changes. Further studies are warranted to determine the impact of these findings on clinical outcomes. Trial registration number: NCT02480205 .